A systematic review of the use of health services by immigrants and native populations. Issue 1 (December 2016) - Sarría-Santamera, Antonio; Hijas-Gómez, Ana; Carmona, Rocío; Gimeno-Feliú, Luís
Abstract Background Changes in migration patterns that have occurred in recent decades, both quantitative, with an increase in the number of immigrants, and qualitative, due to different causes of migration (work, family reunification, asylum seekers and refugees) require constant u pdating of the analysis of how immigrants access health services. Understanding of the existence of changes in use patterns is necessary to adapt health services to the new socio-demographic reality. The aim of this study is to describe the scientific evidence that assess the differences in the use of health services between immigrant and native populations. Methods A systematic review of the electronic database MEDLINE (PubMed) was conducted with a search of studies published between June 2013 and February 2016 that addressed the use of health services and compared immigrants with native populations. MeSH terms and key words comprised Health Services Needs and Demands/Accessibility/Disparities/Emigrants and Immigrants/Native/Ethnic Groups. The electronic search was supplemented by a manual search of grey literature. The following information was extracted from each publication: context of the study (place and year), characteristics of the included population (definition of immigrants and their sub-groups), methodological domains (design of the study, source of information, statistical analysis, variables of health care use assessed, measures of need, socio-economic indicators) and main results. Results Thirty-six publications were included, 28 from Europe and 8 from other countries. Twenty-four papers analysed the use of primary care, 17 the use of specialist services (including hospitalizations or emergency care), 18 considered several levels of care and 11 assessed mental health services. The characteristics of immigrants included country of origin, legal status, reasons for migration, length of stay, different generations and socio-demographic variables and need. In general, use of health services by the immigrants was less than or equal to the native population, although some differences between immigrants were also identified. Conclusions This review has identified that immigrants show a general tendency towards a lower use of health services than native populations and that there are significant differences within immigrant sub-groups in terms of their patterns of utilization. Further studies should include information categorizing and evaluating the diversity within the immigrant population.